Differences in Scube1 and Scube2 Gene Expression in Type II Diabetes Mellitus Patients with Dyslipidemia - Saputri, Rahmi Agu; Ali, Hirowati; Tjong, Djong Hon; Anggraini, Debie; Yarni, Sisca Dwi (Jurnal Biologi Tropis, 2025)
The Scube1 gene is expressed in atherosclerosis (plaque buildup in blood vessels), while Scube2 is expressed in DIT (Diffuse Intimal Thickening) which is used to describe diffuse thickening of the intima of blood vessels. This study aims to determine the differences in the expression of the scube1 gene in blood samples of type II DM patients with dyslipidemia and type II DM with non-dyslipidemia and differences in the expression of the scube2 gene in blood samples of type II DM patients with dyslipidemia and type II DM with non-dyslipidemia. With a comparative cross-sectional research method, the sample size of this study was determined based on the Lameshow hypothesis test formula which obtained 18 blood samples of type II DM with dyslipidemia, and 18 blood samples of type II DM with non-dyslipidemia. Blood samples of type II DM patients with dyslipidemia and blood samples of type II DM patients without dyslipidemia showed significantly different expression of the scube1 gene, with a p-value of 0.000. Similarly, blood samples from type II DM patients with dyslipidemia and those from type II DM patients without dyslipidemia showed a significant difference in scube2 gene expression (p = 0.001). Thus, it can be said that the expression of the Scube1 and Scube2 genes is significantly influenced by the complications of diabetes mellitus with dyslipidemia. This happens because it is believed that hyperglycemia in type II DM contributes to endothelial cell dysfunction, which occurs prior to blood vessel damage and results in progressively more severe blood vessel problems. Along with hyperglycemia, type II diabetes also results in dyslipidemia, an alteration in the normal lipid profile. Both dyslipidemia and hyperglycemia contribute to macrovascular and microvascular problems in type II diabetes.